Human γδ T-Cells: From Surface Receptors to the Therapy of High-Risk Leukemias - Pistoia, Vito; Tumino, Nicola; Vacca, Paola; Veneziani, Irene; Moretta, Alessandro; Locatelli, Franco; Moretta, Lorenzo (Frontiers in Immunology, 2018)
γδ T lymphocytes are potent effector cells, capable of efficiently killing tumor and leukemia cells. Their activation is mediated by γδ T-cell receptor (TCR) and by activating receptors shared with NK cells (e.g., NKG2D and DNAM-1). γδ T-cell triggering occurs upon interaction with specific ligands, including phosphoantigens (for Vγ9Vδ2 TCR), MICA-B and UL16 binding protein (for NKG2D), and PVR and Nectin-2 (for DNAM-1). They also respond to cytokines undergoing proliferation and release of cytokines/chemokines. Although at the genomic level γδ T-cells have the potential of an extraordinary TCR diversification, in tissues they display a restricted repertoire. Recent studies have identified various γδ TCR rearrangements following either hematopoietic stem cell transplantation (HSCT) or cytomegalovirus infection, accounting for their “adaptive” potential. In humans, peripheral blood γδ T-cells are primarily composed of Vγ9Vδ2 chains, while a minor proportion express Vδ1. They do not recognize antigens in the context of MHC molecules, thus bypassing tumor escape based on MHC class I downregulation. In view of their potent antileukemia activity and absence of any relevant graft-versus-host disease-inducing effect, γδ T-cells may play an important role in the successful clinical outcome of patients undergoing HLA-haploidentical HSCT depleted of TCR αβ T/CD19+ B lymphocytes to cure high-risk acute leukemias. In this setting, high numbers of both γδ T-cells (Vδ1 and Vδ2) and NK cells are infused together with CD34+ HSC and may contribute to rapid control of infections and leukemia relapse. Notably, zoledronic acid potentiates the cytolytic activity of γδ T-cells in vitro and its infusion in patients strongly promotes γδ T-cell differentiation and cytolytic activity; thus, treatment with this agent may contribute to further improve the patient clinical outcome after HLA-haploidentical HSCT depleted of TCR αβ T/CD19+ B lymphocytes.